Comparative Genomics International Workshop, RECOMB-CG 2010, Ottawa, Canada, October 9-11, 2010. Proceedings - Tannier, Eric.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 8th RECOMB International Satellite Workshop on Comparative Genomics, RECOMB-CG 2010, Ottawa, Canada, in October 2010. This workshop is devoted to bringing together scientists working on all aspects of comparative genomics, from computer scientists, mathematicians and statisticians working on novel computational approaches for genome analysis and comparison, to biologists applying these computational tools to study the structure and the evolution of prokaryotic and eukaryotic genomes. The 24 papers presented were carefully reviewed and selected from 35 submissions. The papers enrich the combinatorics of genome rearrangements, while gene order phylogenies are getting more and more accurate, thanks to a mixing of combinatorial and statistical principles, associated with rapid and thoughtful heuristics. Several papers tend to refine the models of genome evolution, and more and more genomic events can be modelized, from single nucleotide substitutions in whole genome alignments to large structural mutations or horizontal gene transfers.
Keywords: Computer science; Computer software; Computational complexity; Algebra -- Data processing; Bioinformatics; Biology -- Data processing; Computer Science; Computational Biology/Bioinformatics.; Computer Appl. in Life Sciences; Bioinformatics; Symbolic and Algebraic Manipulation; Discrete Mathematics in Computer Science; Algorithm Analysis and Problem Complexity